Activation of PGC‐1α via isoliquiritigenin‐induced downregulation of miR‐138‐5p alleviates nonalcoholic fatty liver disease. (18th January 2022) - Wang, Lu; Wang, Xiaohui; Kong, Lina; Li, Yingying; Huang, Kai; Wu, Jingjing; Wang, Changyuan; Sun, Huijun; Sun, Pengyuan; Gu, Jiangning; Luo, Haifeng; Liu, Kexin; et al.
Abstract: Nonalcoholic fatty liver disease (NAFLD), a metabolic disease, has received wide attention worldwide. However, there is no approved effective drug for NAFLD treatment. In the study, H&E and Oil Red O staining were employed to detect liver histopathological changes and the accumulation of lipid droplets. Quantitative real‐time PCR, Western blot, bioinformatics, luciferase assay, immunofluorescence staining, reactive oxygen species (ROS), and siRNA were used to further elucidate the mechanism of isoliquiritigenin (ISL) against NAFLD. The results showed that ISL significantly reduced the liver‐to‐body weight ratios and biochemical index. And the staining results showed that ISL remarkedly ameliorated liver histopathological changes of NAFLD. Furthermore, ISL significantly increased the levels of PPARα, CPT1α, and ACADS, which were involved in lipid metabolism, and inhibited the ROS, TNF‐α, IL‐1β, and IL‐6 expression by activating PGC‐1α. Bioinformatics and luciferase assay analysis confirmed that miR‐138‐5p might bind to PGC‐1α mRNA in NAFLD. Importantly, the expression of miR‐138‐5p was increased in the NAFLD, which was significantly decreased by ISL. In addition, the miR‐138‐5p inhibitor also promoted lipid metabolism and inhibited inflammatory response in NAFLD via PGC‐1α activation. The above results demonstrate that ISL alleviates NAFLD through modulating miR‐138‐5p/PGC‐1α‐mediated lipid metabolism and inflammatory reaction in vivo and in vitro.